Human Capital Accumulation, Education and Earnings Inequality - Uwe Sunde (Institute for the Study of Labor (IZA), 2001)
This paper attempts to add to the understanding of the causes for the differing recent developments in inequality in OECD countries. The similarity of shocks and technological changes affecting these countries suggests that interactions of these shocks and countryspecific institutions are responsible for the diverging inequality patterns. The paper suggests a channel complementary to those investigated in recent contributions, focusing on the impact of education. A microfoundation of human capital formation is proposed, emphasizing heterogeneity of individuals and multidimensionality of human capital. The reactions in individual behavior triggered by technological change are crucially affected by the education system and are shown to be responsible for the divergent developments in inequality.
Keywords: J31; O30; E20; J30; 330; Inequality; ability biased technological change; education system; human capital formation; Bildungsinvestition; Technischer Fortschritt; Lohnstruktur; Einkommensverteilung; Bildungswesen; Schätzung; Vergleich; OECD-Staaten